Implementation Strategy for MSMEs D'Celup Chicken Crispy in the city of Padang, West Sumatra - Rosiani, Indah; Yunita, Nika; Lase Afrillia, Usni; Nila Sari, Vivi (AMK : Abdi Masyarakat UIKA, 2023)
This study aims to find out how the condition of D'Celup Chicken Crispy MSMEs determines what implementation is right for these MSMEs in developing their business through strategic management. The research was conducted on the Lubuk Begalung highway, Padang city, West Sumatra. This business was founded by Mr. Ridho and his brother in 2023, more precisely it has only been operating for three months and is experiencing development every day because it was established right close to the university so that many students make Mr. Rido's business a choice of lunch and dinner. Mr. Ridho as CEO said that opening a crispy chicken business because of his passion for chicken, the idea arose to establish a chicken business in Padang City.